Free IL-12p40 monomer is a polyfunctional adaptor for generating novel IL-12-like heterodimers extracellularly. - Abdi, K; Singh, N; Spooner, E; Kessler, B; Radaev, S; Lantz, L; Xiao, T; Matzinger, P; Sun, P; Ploegh, H (American Association of Immunologists, 2014)
IL-12p40 partners with the p35 and p19 polypeptides to generate the heterodimeric cytokines IL-12 and IL-23, respectively. These cytokines play critical and distinct roles in host defense. The assembly of these heterodimers is thought to take place within the cell, resulting in the secretion of fully functional cytokines. Although the p40 subunit alone can also be rapidly secreted in response to inflammatory signals, its biological significance remains unclear. In this article, we show that the secreted p40 monomer can generate de novo IL-12-like activities by combining extracellularly with p35 released from other cells. Surprisingly, an unbiased proteomic analysis reveals multiple such extracellular binding partners for p40 in the serum of mice after an endotoxin challenge. We biochemically validate the binding of one of these novel partners, the CD5 Ag-like glycoprotein, to the p40 monomer. Nevertheless, the assembled p40-CD5L heterodimer does not recapitulate the biological activity of IL-12. These findings underscore the plasticity of secreted free p40 monomer, suggesting that p40 functions as an adaptor that is able to generate multiple de novo composites in combination with other locally available polypeptide partners after secretion.